Framing Analysis of Blasphemy News by Isa Zega in the Practice of Umrah in Suara.com and Viva.co.id - Nanda Alfira Damayanti; Prima Ayu Rizqi Mahanani; Fuad Faizi (Journal of Communication, Sustainability, and Empowerment, 2025)
The case of alleged religious blasphemy involving Isa Zega, a transgender social media influencer who performed Umrah wearing a Shari headscarf and was in the women's section, has sparked a strong reaction from the public. This incident relates to issues of religion, gender identity, and freedom of expression. This research explores how Suara.com and Viva.co.id frame their reporting on this matter using the framing model by Pan and Kosicki on 12 news articles published from November to December 2024. The analysis results show that Suara.com delivers news in a neutral manner and provides space for clarification, while Viva.co.id emphasizes elements of religious violation by quoting religious figures. From the perspective of Islamic journalism, Suara.com is considered to better reflect the principles of journalistic ethics compared to Viva.co.id.